2013
DOI: 10.12944/cwe.8.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Odour Pollution Measurement from Refuse Derive Fuel Operations Using Odour Concentration Meter (OCM) XP-329

Abstract: There has been a dearth on studies of odour pollution in Malaysia due constraints such as lack of measurement equipments, guidelines and legal act for such operational endeavour. Despite the media publication on odour pollution, actions and enforcement were ineffective due to limitations in regulations and operationals standards.In particular, scientific studies on odour concentrations and intensity were difficult to be implemented due to lack of equipments for measuring the phenomenon.Comparatively, researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Livestock excrement is a major source of environmental pollution and poses significant risks to the environment and public health. As the livestock industries have been increasing rapidly [1], unsurprisingly, the amount of livestock excrement has been increasing accordingly. Reports showed that the annual production of livestock excrement in Finland, the EU-27, China, the UK, Indonesia, the USA, and Iran reached 1.60 × 10 10 (wet weight, in 2011) [2], 1.50 × 10 9 tons (dry weight, in 2014) [3], 6.90 × 10 6 tons (dry weight, in 2015) [4], 8.34 × 10 10 tons (dry weight, in 2016) [5], 7.00 × 10 10 tons (dry weight, in 2016) [6], 3.50 × 10 10 tons (dry weight, in 2016) [2], and 2.00 × 10 9 tons (dry weight, in 2017) [7], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock excrement is a major source of environmental pollution and poses significant risks to the environment and public health. As the livestock industries have been increasing rapidly [1], unsurprisingly, the amount of livestock excrement has been increasing accordingly. Reports showed that the annual production of livestock excrement in Finland, the EU-27, China, the UK, Indonesia, the USA, and Iran reached 1.60 × 10 10 (wet weight, in 2011) [2], 1.50 × 10 9 tons (dry weight, in 2014) [3], 6.90 × 10 6 tons (dry weight, in 2015) [4], 8.34 × 10 10 tons (dry weight, in 2016) [5], 7.00 × 10 10 tons (dry weight, in 2016) [6], 3.50 × 10 10 tons (dry weight, in 2016) [2], and 2.00 × 10 9 tons (dry weight, in 2017) [7], respectively.…”
Section: Introductionmentioning
confidence: 99%